PT PERTAMINA GAS’ STRATEGIC ROLE IN SUPPORTING SDGS: FOCUS ON CLEAN ENERGY TRANSITION AND CLIMATE RESILIENCE - Putra, Rio Anggara; Bhayangkara, Ida Bagus Ketut (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Clean energy transition and climate resilience are two main pillars that support the achievement of the Sustainable Development Goals (SDGs), especially SDG 7 (Affordable and Clean Energy) and SDG 13 (Addressing Climate Change). PT Pertamina Gas (Pertagas), a subsidiary of PT Pertamina (Persero), plays a strategic role in the development of natural gas infrastructure and distribution as a cleaner and more efficient transition energy. Pertagas strengthens its commitment to reducing greenhouse gas emissions and increasing national energy resilience through decarbonization programs, natural gas network development, and renewable energy use initiatives. This study highlights various strategic efforts made by Pertagas, the challenges faced in their implementation, and real contributions to the SDGs targets. The results of the analysis show that synergy between corporate policies and national development directions is the key to success in accelerating a sustainable energy transition that is responsive to the climate crisis